Plantas medicinais utilizadas pelos alunos da EJA da Escola Estadual Silva Dourado, em Arraias - Tocantins - Almeida, Vilany Bispo de Ramos (Universidade Federal do Tocantins, 2022)
The traditional use of medicinal plants is what many communities have as an alternative to preserve health or treat diseases, through the perception of its curative power. The objective of this work was to carry out a survey of plant species for medicinal purposes, used by students attending EJA (Youth and Adult Education) at Colégio Estadual Silva Dourado in the city of Arraias - Tocantins. It is a qualitative research in the field, carried out through the application of questionnaires containing questions regarding plant species for medicinal purposes, regarding their use, form and quantity used by the research participants, applied to the treatment of diseases mentioned by students in your family bosom. Data collection was carried out through the application of semi-structured questionnaires, within the classroom. Most of the participants were women in almost all classes, and they were the ones who showed the most knowledge about plants for medicinal purposes. Students varied between 1st, 2nd and 3rd grade of High School, and 7th and 8th year of Elementary School. This study made it possible to recognize important aspects regarding use, active principle, clinical indication and knowledge of the medicinal species used by the students of EJA at Colégio Silva Dourado.